Perencanaan Strategis SI/TI dengan Metode Ward And Peppard (Studi Kasus Pada Dinas Pendidikan Dan Kebudayaan Purbalingga) - Wulandari, Sevira; Fernandez, Sandhy (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The Education and Culture Office (DINDIKBUD) of Purbalingga Regency is one of the offices in Central Java Province. DINDIKBUD is an institution that functions as an education and culture service under the KEMENDIKBUD. The implementation of Information Systems and Information Technology (SI/TI) as a development in fulfilling the vision and mission at DINDIKBUD needs to be supported by a good plan. Currently, the utilization of SI/TI at DINDIKBUD has not been maximized due to the lack of human resources in the IT field, the lack of integration between SI/TI, the absence of SI/TI priorities, there is no standard operating procedure (SOP) related to SI/TI, and the DINDIKBUD website is not up to date. Data collection used interview method with the Head of DINDIKBUD and some related staff, observation and also studied the existing strategy plan document. This research aims to create a proposed SI/TI strategy document at DINDIKBUD as a long-term guide for the use of SI/TI in carrying out organizational activities and operations. This research is a descriptive qualitative research using Ward and Peppard method. The result of this research is an SI/TI strategy document that contains analysis of internal and external business strengths and weaknesses, analysis of internal and external SI/TI strengths and weaknesses, analysis of current conditions, analysis of future conditions, gap analysis, and preparation of future application portfolios. This strategy planning resulted in 9 SI strategies, 9 IT strategies, and 9 SI/TI management strategies along with a roadmap to map the determination of the strategy implementation year.